EFFECT OF POTATO YELOW VEIN: TRANSMITED BY THE VECTOR TRIALEURODES VAPORARIORUM ( WESTWOOD) IN POTATO - SALDARRIAGA-V., ALFREDO; ALVAREZ, ANGELA M.; JARAMILLO, JORGE E. (Revista Colombiana de Entomología, 1988)
There is scarce knowledge of the disease "potato yellow vein", its etiology, physiology, epidemiology, and ecology. It has been proved, under greenhouse conditions, that the greenhouse whitefly Trialeurodes vaporariorum (Westwood) (Homoptera: Aleyrodidae) is a vector of the disease. Field studies were conducted in order to evaluate distribution, severity, and losses due to "potato yellow vein" in the potato growing area of Antioquía (Colombia); these data were correlated with population studies of the vector and several of its plant hosts. The disease causes yield reduction of 41,82% in var "capiro" and of 53,760/o in var "picacho". There was a significant reduction in tubers, regarding their size and the number of them. None of the plant parts: stems, leaves, flowers, tubers suffered structural deformations. Vein yellowing starts 25 days after sprout development, it reaches its peak at 50-60 days ago; but does not show anymore as soon as plant maturity 40 and 100% occurred in El Santuario, Marinilla, Guarne, and Rionegro area at 2.100 m.a.s.I., where mixed crops potato-dry bean allow explosive development of the insect vector, a major pest of dry beans. The lowest incidence of disease occurred in the La Unión area, at 2.500 m.a.s.l.